PENGARUH MODEL PEMBELAJARAN GROUP INVESTIGATION (GI) TERHADAP HASIL BELAJAR IPAS PESERTA DIDIK KELAS IV SEKOLAH DASAR - Nanda Ayu Setiawati; Putri Roka Ismail; Mutiara Lestari Aritonang (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2026)
This study aims to determine the effect of the Group Investigation (GI) learning model on the learning outcomes of fourth-grade students in the subject of Cultural Diversity in My Country at SDN 064985 Medan Helvetia in the 2024/2025 Academic Year. The type of research used is a quasi-experimental design with a nonequivalent control group design. The study population was all fourth-grade students consisting of two classes with a total of 44 students. The research sample used a saturated sampling technique, namely class IV-A as the experimental class totaling 21 students and class IV-B as the control class totaling 23 students. The research instruments were multiple-choice tests, observation, and documentation. Data were analyzed using normality tests, homogeneity tests, and hypothesis tests. The results showed that the average pretest score of the experimental class was 57.62 and the control class was 50.65. After being given treatment using the Group Investigation model, the average posttest of the experimental class increased to 83.33, while the control class was 77.39. The results of the analysis show that the Group Investigation learning model has a significant effect on the science learning outcomes of grade IV students at SDN 064985 Medan Helvetia.